2010
DOI: 10.1209/0295-5075/92/47007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent chirped coherent phonon dynamics in Bi 2 Te 3 using high-intensity femtosecond laser pulses

Abstract: Degenerate pump-probe reflectivity experiments have been performed on a single crystal of bismuth telluride (Bi 2 Te 3 ) as a function of sample temperature (3K to 296K) and pump intensity using ∼ 50 femtosecond laser pulses with central photon energy of 1.57 eV. The time resolved reflectivity data show two coherently generated totally symmetric A 1g modes at 1.85 THz and 3.6THz at 296K which blue shift to 1.9 THz and 4.02 THz, respectively at 3K. At high photoexcited carrier density of ∼ 1.7 × 10 21 cm −3 , t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 32 publications
4
37
0
Order By: Relevance
“…We note that a similar 3.6 THz mode has been previously observed in a number of time-domain studies on Bi 2 Te 3 [12,15,16]. For instance, in Refs.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…We note that a similar 3.6 THz mode has been previously observed in a number of time-domain studies on Bi 2 Te 3 [12,15,16]. For instance, in Refs.…”
Section: Resultssupporting
confidence: 85%
“…In later studies [13,14], the modes at 1.85 THz and 4.02 THz were assigned to two allowed A 1g modes, in agreement with spontaneous Raman measurements [9,10]. The detailed time-domain study [15] in which both the temperature and power dependence of coherent phonons were measured confirmed that the higher-frequency coherent phonon mode, which appears with 3.6 THz frequency at room temperature and increases to 4.0 THz at helium temperature, is an A This high-frequency mode acquires two orders of magnitude higher positive chirp at the lowest temperatures and high pump fluence as compared to the A (I) 1g phonon. Our previous study [16] revealed that depending on the pump polarization with respect to the crystal orientation one can see either only two fully symmetric coherent phonons at 1.8 and 4.0 THz, or, in addition, the mode at 3.6 THz assigned tentatively to a doubly degenerate E (II) g phonon.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations